Antimicrobial resistance pattern of Gram-positive bacteria during three consecutive years at the nephrology ward of a tertiary referral hospital in Shiraz, Southwest Iran - Iman Karimzadeh; Mona Mirzaee; Niloofar Sadeghimanesh; Mohammad Mahdi Sagheb (Wolters Kluwer Medknow Publications, 2016)
Objective: The aim of the present study was to determine the pattern of antimicrobial resistance of Gram-positive bacteria during three consecutive years at the nephrology ward of Namazi Hospital in Shiraz, Southwest of Iran. Methods: During a 3-year period from 2013 to 2015, data of all biological samples of hospitalized patients at the adult nephrology ward of Namazi Hospital were sent to the central laboratory for identification of Gram-positive microorganisms and subsequently, their antimicrobial susceptibility testing by Kirby-Bauer disc diffusion method were analyzed in a retrospective manner. Findings: Coagulase-negative Staphylococci (CONS) (38.5%), Staphylococcus aureus(25.4%), and Enterococcus spp. (23.8%) were the most common isolated Gram-positive bacteria from all biological samples. All Enterococcus spp. isolates within the 3 years were resistant to oxacillin. The rate of vancomycin-resistant enterococci (VRE) increased from 40.63% in 2013 to 72.73% in 2015. Enterococcus spp. resistance rates to aminoglycosides during 3 years were above 85%. The frequencies of oxacillin-resistant S. aureus (ORSA) in 2013, 2014, and 2015 were 95.24%, 80.95%, and 36.36%, respectively. Two out of 11 (6.67%) S. aureus isolates were resistant to vancomycin. More than 90% of CONS were sensitive to vancomycin within the study period. The frequency of gentamicin-resistant CONS ranged from 40% to 57.14%. Conclusion: The rates of ORSA, VRE, and aminoglycoside-resistant CONS as well as Enterococcus spp. in our clinical setting were considerably high and concerning. These may be due to the failure or lack of infection control activities and antimicrobial selection pressure.